Socio-geographic research of the transformation of the structure of the settlement system of the Polissya region of Ukraine (on the example of the Rokytne territorial community). - Karpiuk, Zoia K.; Khmeliovskyi, Yurii L.; Pavlovska, Tetiana S.; Chyzhevska, Larysa T.; Kacharovskyi, Roman E. (My University, 2024)
The relevance of socio-geographical studies of the transformation of population settlement systems, particularly of disappeared rural settlements at the local level, is due to their very essence as expressions of multifaceted information about the spatio-temporal aspects of the evolution of socio-geosystems, indicators of territory development, essential component of preserving the historical and cultural heritage of the region, and an important resource for the development of the tourism and recreation sphere of territorial communities. The article analyzes the typology of localities, the dynamics of development, quantitative changes in the system of population settlement, particularly the disappeared localities of northern Polissia, as an example of the territory that, according to the modern administrative-territorial division, lies within the boundaries of the Rokytne territorial community of the Rivne Oblast. During the work, the following research methods were used: source analysis – to determine the types of information data and clarify the completeness of their reflection of historical events; systematic approach, comparative-geographical analysis, general historical methods – to reveal the features of the structure of the settlement system of the northern Polissia region, establish the spatial and temporal trends of the territory’s development, find out the former location of localities, the reasons, conditions, and periods of the disappearance of many localities; cartographic – for finding source data, its analysis, and creating a list-catalogue with a cartographic display of lost localities; expeditionary – to obtain actual data. A general algorithm for researching rural settlements lost today at the local level is proposed. The main factors were clarified regarding the periods of disappearance of about 250 localities of various social types due to the destabilization of the situation caused by socio-economic changes, military aggression, deportation and collectivization; their spatial distribution is mapped. The need for further research on the disappeared localities as important indicators of settlement and resettlement processes as well as the development of population resettlement systems in the northern Polissia region and forecasting the future states of socio-geosystems is substantiated.
Keywords: resettlement system; disappeared localities,; type of localities; village, hamlet; stockade, colony; settlement; border region; territorial community; Rokytne territorial community; Rivne Oblast